Managing Transition in Patients Treated with Growth Hormone - Hauffa, Berthold P.; Touraine, Philippe; Urquhart-Kelly, Tanya; Koledova, Ekaterina (Frontiers in Endocrinology, 2017)
Full abstract will not fit - please see attached document for full abstract (this is due to being changed from manuscript to a Perspective article) Growth hormone (GH) promotes growth in children, but is also essential for bone strength, body composition, metabolic factors such as lipid profile and maintenance of quality of life. The Merck KGaA (Germany) funded ‘360° GH in Europe’ meeting, held in Lisbon, Portugal, in June 2016, comprised three sessions entitled ‘Short Stature Diagnosis and Referral’, ‘Optimizing Patient Management and Adherence’ and ‘Managing Transition’. The scientific program covered all stages of pediatric GH treatment, and reported here are the outcomes of the third session of the meeting, which considered transition from pediatric GH treatment to teenage and young adult GH therapy. A large number of patients with chronic diseases, including GH deficiency, drop out of therapy during the transition period. Multiple factors are associated with this, such as lack of understanding of the disease process, insufficient knowledge of treatment options, the patient becoming more independent, and requirement for interaction with a new set of healthcare workers. Education regarding disease management and treatment options should be provided from an early age and right through the transition period. However, endocrine specialists will view the transition period differently, depending on whether they are pediatric endocrinologists who mainly deal with congenital diseases in which auxology is important, or adult endocrinologists who are more concerned with body composition and metabolic factors. Viewpoints of both a pediatric and an adult endocrine